Review of John Rawls' Theory of Justice in Penal Mediation as a Settlement for Minor Offenses at Al-Ishlah Male Islamic Boarding School, Malang - Rofrofil Akmal, Ahmad Wildan; Alwi, Khanabi Alwi; Wibowo, Erik (Lembaga Yasin AlSys, 2025)
This study examines the resolution of minor criminal offenses committed by students at Pondok Pesantren Putra Al-Ishlah, Singosari, Malang, through penal mediation, analyzed within the framework of John Rawls’ theory of justice. Offenses such as petty theft, verbal insults, and minor vandalism are addressed internally through restorative measures rather than formal legal proceedings. Employing a qualitative field research approach, data were collected through interviews with pesantren administrators and teachers, along with the analysis of documented cases from 2020 to 2024. The pesantren applies restorative and educational sanctions, such as Qur’an recitation, performing the call to prayer, or repairing damaged property while engaging offenders, victims, and guardians in a deliberative mediation process. The findings demonstrate that this approach embodies Rawls’ two key principles of justice: the assurance of equal basic liberties and the application of the difference principle in promoting fairness. Penal mediation at the pesantren functions not only as a deterrent to future misconduct but also as a means of reconciliation and moral development, reinforcing community cohesion. This culturally grounded model of restorative justice offers an alternative framework for addressing juvenile misconduct in educational institutions, illustrating the practical integration of moral philosophy, disciplinary methods, and character education in a faith-based setting.